PENGARUH MUTASI DAN PELATIHAN TERHADAP KINERJA PERSONIL BINTARA DI POLRES SAROLANGUN - Fathiyah Fathiyah; Bahrina Liapijannah (J-MAS (Jurnal Manajemen dan Sains), 2016)
The research aims to obtain a description or explanation on the implementation of the mutation and training in Polres Sarolangun and factors affecting the implementation of mutation in Polres Sarolangun a commissioned officer.            This research method used is descriptive of analysis with the goal to give a description or painting the situation in a systematic, factual and accurate on the implementation of mutation and training of personel on the performance specialist in Polres Sarolangun. Were analysed qualitatively better data which are quantitative and qualitative based on the report and note that in the field.  With data collection techniques study literature and field studies namely the questionnaire. Based on the results of the testing of hypotheses of any result was obtained on the variable significant.